Passive highly dispersive matching network enabling broadband electromagnetic absorption - Pardha S. Nayani; Morteza Moradi; Pooria Salami; Younes Ra’di (Nature Communications)
Abstract In numerous applications from radio to optical frequencies including stealth and energy harvesting, there is a need to design electrically thin layers capable of perfectly absorbing electromagnetic waves over a wide bandwidth. However, a theoretical upper bound exists on the bandwidth-to-thickness ratio of metal-backed, passive, linear, and time-invariant absorbing layers. Absorbers developed to date, irrespective of their operational frequency range or material thickness, significantly underperform when compared to this upper bound, failing to exploit the full potential that passive, linear, and time-invariant systems can provide. Here, we introduce a new concept for designing ultra-thin absorbers that enables absorbing layers with a record-high bandwidth-to-thickness ratio, potentially several times greater than that of absorbers designed using conventional approaches. Absorbers designed based on this concept can achieve a bandwidth-to-thickness ratio arbitrarily close to the ultimate bound. Utilizing this concept, we design and experimentally verify an absorber yielding a very high bandwidth-to-thickness ratio.